Türkiye’de uçak üretimi: 1936-1950 - Işık, Zekiye (My University, 2016)
Cumhuriyetin ilânıyla birlikte uçak üretimi Türkiye’de özel ehemmiyet verilmesi gereken bir konu hâline gelmiştir. Bu düşünce, dünyada bu yönde yürütülen çalışmaların yakından takibi ile mümkün olabilmiştir. Bu çalışmada dünyada uçak üretiminin zamanla ekonomik bir kavrama dönüşmesinden yola çıkılarak Türkiye’deki uçak üretiminin özel teşebbüs girişimiyle ekonomiyi nasıl şekillendirdiği, Nuri Demirağ ismi üzerinden ele alınmıştır. Bu çalışmanın amacı ülkemizdeki uçak üretimi bağlamında Nuri Demirağ’ın girişimden yola çıkarak, havacılık sektörünün ekonomi içerisindeki yerini tespit edip sektörün gelecekle ilgili durumunu netleştirmek olmuştur. İlk bölümde, dünyada uçağın ilk ortaya çıkışıyla beraber üretim süreci içerisinde yer alıp ekonomik bir kavram ihtiva edecek hâle dönüşmesi ele alınmıştır. Böylelikle pek çok hava aracının uçağın oluşumuna sağladığı katkıdan yola çıkarak, uçak üretiminin bir sektöre dönüşümü ortaya konulmuştur. İkinci bölümde, dünya savaşının ağır sanayiyi gerekli kılmasıyla özellikle 1920-1950 yılları arasında havacılık sektörüne hem devletin hem de özel teşebbüsün verdiği önem belirtilmiştir. Ayrıca Vecihi Hürkuş ve Nuri Demirağ gibi güçlü girişimcilerin neden uçağa yönelik yatırımlara yoğunlaştığı açığa çıkarılırken tüm bu çalışmaların neden sonlandırıldığı irdelenmiştir. Üçüncü bölümde, havacılık sektörünün mevcut durumu incelenerek özellikle 1983 yılı sonrasındaki gelişmeler üzerinde durulmuştur. Bu sayede mevcut durumda sektörün güçlü ve zayıf yönleri belirtilerek nelerin sektöre yönelik fırsat veya tehdit olabileceğine ulaşılmıştır. Ek olarak sektörle bağlantılı kollarda ve sektörün ana bileşenlerindeki sorunlara değinilerek oluşabilecek engellerin aşılmasına yönelik öngörülerde bulunulmuştur. Nuri Demirağ, Türkiye Havacılık Sektörü, Türkiye Uçak Ekonomisi

The airplane manufacture became a topic of high importance with the founding of the Republic of Turkey. The idea of manufacturing airplanes in Turkey was a reflection of the works being carried out in the world at the time. In this study, I have discussed how the airplane manufacture became an economical concept in the world over the course of time and how the airplane manufacture by the private ventures in Turkey shaped the economy, with a special focus on Nuri Demirağ’s efforts. The purpose of this study is to determine the position of the aviation industry within the economy and shed light onto the future of the industry with reference to Nuri Demirağ’s venture within the airplane manufacture activities in our country. In the first part, I have discussed the invention of the airplane and its transformation into an economical concept as a part of the manufacturing industry. Thus, taking the contributions from many aircrafts during the creation process of the airplane in consideration, the transformation of the airplane manufacture into an industry is revealed. With the world wars necessitating a heavy industry, I have underlined in the second part, the importance attributed to the aviation industry both by the public and private ventures, especially between 1920 and 1950. In addition I have pointed out to the reasons as to why powerful entrepreneurs such as Vecihi Hürkuş and Demirağ focused on airplanes in their ventures and discussed why their works were terminated. In the third part, I have analyzed the current situation of the aviation industry and elaborated on the developments after 1983. This way I have been able to determine the strengths and weaknesses of today’s aviation industry, and uncover potential opportunities and threats waiting for it. In addition, I have addressed the problems within the main components of the industry and in other branches attached to the industry, and made some predictions about how to solve potential future problems. Nuri Demirağ, Turkish Aviation Industry, Turkish Airplane Economy
Keywords: Türkiye; Uçak endüstrisi